Pertanggungjawaban Pidana Rumah Sakit Terhadap Malpraktek Medik Di Rumah Sakit - Robert Valentino Tarigan; mahmud mulyadi; M Ekaputra; Mahmul Siregar (Iuris Studia: Jurnal Kajian Hukum, 2021)
Hospital in implementing health services is not always the medical service provided by health workers in the hospital, it can provide the results expected by all parties. Not a few hospitals due to the negligence of their doctors in providing health services made the mistake of committing medical malpractice. Article 46 of Law Number 44 Year 2009 states that